INFORMATION TECHNOLOGY EDUCATION IN ELEMENTARY AND SECONDARY EDUCATION: CONTRIBUTIONS OF MAKER CULTURE AND THE STEAM APPROACH TO ACTIVE LEARNING - de Sousa, Alexandre Vidal; Portácio, Denilson Albano; da Silva, Fábio Fares Marques; da Silva, Fernanda Maria Diniz; da Silva, Fernângela Diniz; Cajado, Francisco José Lopes; Santana, Givanildo Ximenes; Fontes, Irene Mendes; Lima, Leni Oliveira da Silva; Araujo, Maria Antônia do Socorro Rabelo; Gomes, Rickardo Léo Ramos; Caracas Neto, Roberto Augusto (Seven Editora, 2026)
Information Technology Education in Elementary and Secondary Education has followed contemporary transformations that demand more dynamic, integrated, and student-centered pedagogical practices. In this context, Maker Culture and the STEAM approach have gained prominence by promoting learning experiences based on experimentation, collaboration, and the articulation between different areas of knowledge, contributing to the construction of educational pathways more aligned with current demands. The present study aims to analyze how Maker Culture and the STEAM approach contribute to the promotion of active learning in Information Technology Education in Elementary and Secondary Education. Regarding the methodological procedures, the investigation was guided by a qualitative approach, since it sought to understand educational phenomena through the interpretation of meanings, practices, and relationships established within the analyzed context. As a research strategy, a bibliographic review was adopted, understood as a procedure that makes it possible to identify, systematize, and examine existing scientific productions, favoring the construction of a consistent theoretical framework articulated with the theme under study. In summary, the study demonstrates that the integration between Maker Culture and the STEAM approach in Information Technology Education favors the promotion of active learning in Elementary and Secondary Education by articulating theoretical foundations and pedagogical practices that stimulate student participation and the development of competencies aligned with contemporary educational demands.